Reverse transcription-PCR detection of hepatitis G virus - Volker Schlueter; S. Schmolke; Klaus Stark; Georg Heß; Beatus Ofenloch-Haehnle; Anna Maria Engel (1996)
Hepatitis G virus (HGV) was recently identified as a new member of the Flaviviridae, but its clinical significance is still unclear. Since no immunoassay for the diagnosis of HGV is available, we developed a sensitive reverse transcription-PCR (RT-PCR) assay to facilitate the detection of the viral genome by mass screening in the clinical laboratory. Sequences within the 5'-noncoding region and within the putative NS5a region are independently amplified in the presence of digoxigenin-11-dUTP and are detected by hybridization with biotinylated capture probes binding to a streptavidin-coated matrix. Semiquantitative Enzymun-Test DNA detection via chemiluminescence can be performed either in a microtiter plate format or on fully automated ES 300 machines. We were able to detect at least 8 x 10(2) genome equivalents per ml of serum using both primer pairs. HGV was shown to be present in 43 of 130 (33%) serum samples from intravenous drug abusers with a high risk of parenteral exposure. However, only two of the patients were positive when the NS5a primers only were used, and only one patient was positive when only the 5'-noncoding region primers were used, demonstrating the increased sensitivity of HGV detection with two sets of primers. Among these patients, there was no obvious correlation with other viral infections like hepatitis B virus, hepatitis C virus, or human immunodeficiency virus. Within a blood donor panel, 3 of 92 (3%) samples were found to be HGV positive, suggesting that donated blood may need to be screened for HGV.